2024
DOI: 10.3389/fimmu.2023.1298583
|View full text |Cite
|
Sign up to set email alerts
|

High-grade synovitis associates with clinical markers and response to therapy in chronic inflammatory arthritis: post hoc analysis of a synovial biomarkers prospective cohort study

Carlo Garaffoni,
Marianna Tamussin,
Ilaria Calciolari
et al.

Abstract: BackgroundInflammatory arthritis (IAs), such as rheumatoid arthritis (RA) and psoriatic arthritis (PsA), are characterized by the presence of chronic synovitis. The Krenn’s synovitis score (KSS), a simple tool detectable by haematoxylin/eosin staining of synovial biopsy samples, allows the discrimination between high-grade and low-grade synovitis. The aim of this study was to identify the clinical associations of KSS and to evaluate the relationship between high-grade synovitis and treatment response in IA pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 65 publications
(90 reference statements)
0
0
0
Order By: Relevance
“…For example a study reported a significantly higher uptake of [68 Ga]Ga-FAPI-04 in synovial tissue compared to non-responders (25). A synovial biopsy study assessed 53 inflammatory arthritis patients including 34 RA: in the follow-up study high-grade synovitis were significantly associated with DAS28 remission, ACR20/50 response, and Boolean 2.0 remission (26).…”
Section: Biomarkersmentioning
confidence: 99%
“…For example a study reported a significantly higher uptake of [68 Ga]Ga-FAPI-04 in synovial tissue compared to non-responders (25). A synovial biopsy study assessed 53 inflammatory arthritis patients including 34 RA: in the follow-up study high-grade synovitis were significantly associated with DAS28 remission, ACR20/50 response, and Boolean 2.0 remission (26).…”
Section: Biomarkersmentioning
confidence: 99%